2021
DOI: 10.47191/afmj/v6i11.01
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Digital Money on Economic Growth in Kenya

Abstract: The growth of the economy is a concern to many because it has an influence on the progress of a country and its citizens. It is expected that an economy with a highly advanced digital money system should also experience high economic growth. However, statistics indicate that the economic growth rate in Kenya has been fluctuating and has failed to grow consistently despite numerous policy interventions. This study sought to establish the influence of digital money on Economic Growth in Kenya. The study incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, Olubukola, et al (2023) result disagreed with this study finding, their findings indicates that volume of mobile banking positively and significantly affects gross domestic product. Ramos and Olweny (2021) results from the regression analysis indicated a positive and significant association between mobile banking and gross domestic product in Kenya. Satia and Okle (2020) indicates that mobile banking positively and significantly influences economic growth in the short run and long run in Cameroon H04: Web banking have no positive and significant influence on real gross domestic product.…”
Section: Figure 1: Cumulative Sum Of Square Recursive Residuals Plots...mentioning
confidence: 90%
See 4 more Smart Citations
“…However, Olubukola, et al (2023) result disagreed with this study finding, their findings indicates that volume of mobile banking positively and significantly affects gross domestic product. Ramos and Olweny (2021) results from the regression analysis indicated a positive and significant association between mobile banking and gross domestic product in Kenya. Satia and Okle (2020) indicates that mobile banking positively and significantly influences economic growth in the short run and long run in Cameroon H04: Web banking have no positive and significant influence on real gross domestic product.…”
Section: Figure 1: Cumulative Sum Of Square Recursive Residuals Plots...mentioning
confidence: 90%
“…The benefits of ATM to a bank are: a useful channel to attract and retain more customers, increases cash in your customers hands, provide convenient service for customers, reduces the amount of bad cheques, saves lots of hidden costs etc (Appah & Inini, 2019). The study conducted by Ramos and Olweny (2021) revealed that automated teller machine positively and significantly influences economic growth in Kenya. Olubukola et al (2023) study in Nigeria suggested that volume of automated teller machine transactions positively impact on economic growth of Nigerian economy.…”
Section: Automated Teller Machine (Atm)mentioning
confidence: 99%
See 3 more Smart Citations